3
Another Answer:
2
I get 2 and here is why:
3X / (x^2 + x) = 1
[multiply "both sides" by (x^2 + x)]
3X = x^2 + x
[subtract 3X from both sides]
0 = x^2 - 2X
[divide both sides by X]
0 = x - 2
[add 2 to both sides]
2 = x
... DOUBLECHECK ...
3X / (x^2 + x) = 1
(3 x 2 ) / ( 2^2 + 2 ) = 1
6 / ( 4 + 2 ) = 1
6 / 6 = 1
Chat with our AI personalities
It is x - y + 2 = 0
((15xy2)/(x2+5x+6))/((5x2y)/(2x2+7x+3)) =(15xy2/5x2y)*(2x2+7x+3)/(x2+5x+6) =(3y/x)*(((2x+1)(x+3))/((x+2)(x+3) =(3y(2x+1))/(x(x+2)) =(6xy+3y)/(x2+2x)
9 plus 16=25 3 squared is the same as 3 times three and 4 squared is the same as 4 times 4 3 times 3 + 4 times 4 9 plus 16 = 25
x2 + 8x2 = 9x2
Assuming the thing is as written and there are no brackets missed out then it is just 4 squared times 3 = 16x3=48.